Idiopathic Juxtafoveal Telangiectasia - Haynes, Jessica; Williamson, Jim (Canadian Journal of Optometry, 2017)
Idiopathic Juxtafoveal Telangiectasia (IJT), also called Idiopathic Macular Telangiectasia, is a group of disorders with varying etiologies that share the common finding of telangiectatic vessels in the juxtafoveal region of the macula. IJT is classically divided into three groups, each with clinically dis-tinct findings and differing etiologies. Type I typically occurs unilaterally, primarily affects males, and is thought to be congenital. Vision loss usually results from macular edema. The most common type, II, normally presents bilaterally, has no sex predilection, and is thought to be acquired. Vision loss occurs not from edema, but from retinal atrophy. The last type, III, is extremely rare and is usually found in association with coexisting systemic or neurological disorders. Vision loss most likely results from retinal isch-emia. This paper will describe classifications, clinical findings, etiologies, and treatment options of IJT along with patient case figures.